2019
DOI: 10.1093/annonc/mdz196
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy in the era of immuno-oncology: is it ready for prime-time use for cancer patients?

Abstract: The emergence of immunotherapy in oncology requires the discovery, validation and subsequent adoption of robust, sensitive and specific predictive and prognostic biomarkers for daily practice. Until now, anti-PD-L1 immunohistochemistry (IHC) on tissue sections has been the only validated companion diagnostic test for first-line immunotherapy for advanced and metastatic cancer, notably non-small-cell lung cancer (NSCLC). However, detection of this biomarker presents limitations that have stimulated the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 135 publications
1
136
0
2
Order By: Relevance
“…b Changes in target lesions from baseline to best response or the initial radiographic assessment, as well as treatment information (regimen, line, and response) and PD-L1 expression levels of 10 patients who received ICIs. Abbreviations: PFS -progression-free survival, ICIimmune checkpoint inhibitor, MKI -multi-kinase inhibitor, PD -progression disease, SD -stable disease, PR -partial response of their functions [24], TCR repertoire analysis can be utilized to stratify patients with long survival or screen ICI candidates in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b Changes in target lesions from baseline to best response or the initial radiographic assessment, as well as treatment information (regimen, line, and response) and PD-L1 expression levels of 10 patients who received ICIs. Abbreviations: PFS -progression-free survival, ICIimmune checkpoint inhibitor, MKI -multi-kinase inhibitor, PD -progression disease, SD -stable disease, PR -partial response of their functions [24], TCR repertoire analysis can be utilized to stratify patients with long survival or screen ICI candidates in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The T cell receptor (TCR) repertoire has recently emerged as a novel biomarker [23,24]. Previous pilot studies showed that tumor-infiltrated TCR clonality [25] and peripheral blood T cell receptor repertoire diversity [26][27][28] could have a potential role as predictors of the response to ICI therapy.…”
Section: T Cell Receptor Sequencing and Data Analysismentioning
confidence: 99%
“…It can be detected using standard ELISA assays in patient blood, with high PDL-1 levels associating to adverse prognosis in multiple tumor types. In NSCLC for example, high soluble PDL-1 is associated with adverse prognosis, and studies in melanoma suggest it could even be utilized as a dynamic predictor of durable efficacy to checkpoint inhibitors (Hofman et al, 2019). Mechanistically, it is plausible that elevated soluble PDL-1 levels reflect an immunocompromised/suppressed state, and as such interfere with CPI efficacy (Zhou et al, 2017).…”
Section: Pdl-1 -Is This the Best We Have So Far?mentioning
confidence: 99%
“…It relies on capturing epithelial cell adhesion molecule (EpCAM) positive tumor cells from whole blood, however, its broad clinical value remains elusive. Determining PDL-1 expression on CTCs, in addition to all preceding challenges of this technology (namely false positive or negative assay results) and ability to ensure specificity, heightens the risk for co-isolating cellular populations like myeloid cells, and misidentifying them as CTCs expressing PDL-1 (Hofman et al, 2019).…”
Section: Pdl-1 -Is This the Best We Have So Far?mentioning
confidence: 99%
“…A second example is PD-L1 as one immune checkpoint regulator; it has become an exciting new therapeutic target leading to long lasting remissions in patients with advanced malignancies [14,15]. Kloten et al highlighted the use of CTCs as a complementary diagnostic tool for PD-L1 expression analysis in advanced NSCLC patients [16].…”
mentioning
confidence: 99%